Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T15:06:56+01:00
-5ab + (bc - 2 ab) + 4 cb= -5ab + bc - 2 ab + 4 cb = -7ab+5bc


(5xyz-2xz)+(4zx-7zyx)= 5xyz-2xz+4zx-7zyx = -2xyz+2xz


(m+n) - (2m+3n)=m+n - 2m -3n = -m-2n


(2xy+4y²)-(3yx-2y²= 2xy+4y²-3yx+2y² = 6y²-xy


3abc-(2cab+5bac)= 3abc-2cab-5bac = -4abc


10x²y-(5xy²-8x²y= 10x²y-5xy²+8x²y = 18x²y-5xy²
2010-03-09T15:08:24+01:00
A) -5ab + (bc - 2 ab) + 4 cb= -5ab + bc - 2ab=-7ab+bc
b) (5xyz-2xz)+(4zx-7zyx)=5xyz-2xz+4zx-7zyx
c) (m+n) - (2m+3n)=m+n-2m-3n=-m-2n
d) (2xy+4y²)-(3yx-2y²)=2xy+4y²-3yx+2y²=2xy-3yx+6y²
e) 3abc-(2cab+5bac)=3abc-2cab-5bac
f)10x²y-(5xy²-8x²y)= 10x²y-5xy²+8x²y=18x²y-5xy²

;))
1 2 1
2010-03-09T15:09:34+01:00
-5ab + (bc - 2 ab) + 4 cb= -5ab + bc - 2 ab + 4 cb= -3ab+5bc
(5xyz-2xz)+(4zx-7zyx)=5xyz-2xz+4zx-7zyx=-2xyz+2zx
(m+n) - (2m+3n)= m+n - 2m+3n=-m+4n
(2xy+4y²)-(3yx-2y²=2xy+16y-3xy-4y=-xy+12y
3abc-(2cab+5bac)=3abc-2cab+5bac
10x²y-(5xy²-8x²y=100xy-25xy-64xy=66xy